To replicate, or not to replicate? the creation, use, and dissemination of 3D models of human remains: a case study from Portugal - Alves-Cardoso, Francisca; Campanacho, Vanessa (MDPI, 2022)
Advancements in digital technology have conquered a place in cultural heritage. The widespread use of three-dimensional scanners in bioanthropology have increased the production of 3D digital replicas of human bones that are freely distributed online. However, ethical considerations about such 3D models have not reached Portuguese society, making it impossible to assess their societal impact and people’s perception of how these models are created and used. Therefore, Portuguese residents were asked to take part in an online survey. The ratio of male to female participants was 0.5:1 in 312 contributors. The age ranged between 18 and 69 years. The majority had a higher education degree. Only 43% had seen a 3D model, and 43% considered the 3D replicas the same as real bone. Also, 87% would be willing to allow their skeleton and family members to be digitalized after death, and 64% advocated the controlled dissemination of replicas through registration and login and context description association (84%). Overall, the results suggest agreement in disseminating 3D digital replicas of human bones. On a final note, the limited number of participants may be interpreted as a lack of interest in the topic or, more importantly, a low self-assessment of their opinion on the subject.
Keywords: ethics; biological anthropology; three-dimensional scanning; three-dimensional modeling; human skeletons; heritage; public opinion; Portugal